A CRITICAL SYNTHESIS OF MONETARY POLICY TRANSMISSION, FISCAL MIX, AND REAL SECTOR VOLATILITY: A MULTIDIMENSIONAL REVIEW - Ramadhan, Rizky; Resnawati, Resnawati; Abrori Amin, Fijar (Edunomika Journal : Studies In Education And Development Economics, 2026)
This article aims to synthesize the dynamics of macroeconomic policy transmission through a multidimensional review of the interactions between monetary policy, the fiscal mix, and real sector volatility. Using a systematic critical review approach, this study extracts and evaluates selected scientific literature from 2012 to 2025. The synthesis results show that modern economic stability can no longer be achieved linearly through a single monetary instrument; its effectiveness relies heavily on close coordination with the fiscal mix. Furthermore, the transmission mechanism is shown to operate asymmetrically, with policy effects largely dictated by heterogeneity in household liquidity and debt, financial sector frictions, global spillover turbulence, and the stabilizing role of dual monetary systems (conventional and Islamic) in developing countries. The novelty of this study lies in its integrated mapping, which reveals the weaknesses of linear assumptions in traditional macroeconomic models while highlighting the vulnerabilities of micro-sectoral entities. The implications of this research provide an important contribution to the development of economics and economic education. Academically, these findings encourage the renewal of macroeconomic education curricula, shifting from teaching static equilibrium models to a dynamic economic paradigm that accommodates asymmetry and non-linearity. Practically, this study provides a basis for authorities to design an inclusive policy architecture (policy mix) to protect the real sector from global shocks